Beating the Odds: How Six Post-Secondary Learners Overcame Common Challenges of Attention Deficit Hyperactivity Disorder - Wise, Martha L.; Wise, Barbara L.; Jones, Sarah (Journal of the American Academy of Special Education Professionals, 2022)
Students with ADHD are less likely to enroll in a 4-year college than their neurotypical peers. Persons with Attention Deficit Hyperactive Disorder (ADHD) are characterized not only by executive function challenges but social-emotional and coping struggles. These deficits can lower resilience and cause maladaptive traits to form that lower chances of success in school. This study aimed to examine the commonalities in the personal histories of six adults with ADHD who have attained the level of post-secondary education at a four-year university. Using Seidman’s three-part interview, six successful college attendees diagnosed with ADHD in childhood were interviewed. All participants described themselves as currently thriving. The major themes that emerged from this study were Recovery from Major Life Stumble, Offbeat Pathfinding, Positive Experiences with Authority Figures/Mentors, Thriving in Leadership Positions, Advocating for Those More Vulnerable Than Themselves, and Professional Purpose & Passion. Implications are given for how findings might help educators and other professionals foster resilience and success in students with ADHD.